2016
DOI: 10.4049/jimmunol.1600306
|View full text |Cite
|
Sign up to set email alerts
|

M-CSF Mediates Host Defense during Bacterial Pneumonia by Promoting the Survival of Lung and Liver Mononuclear Phagocytes

Abstract: Gram-negative bacterial pneumonia is a common and dangerous infection with diminishing treatment options due to increasing antibiotic resistance among causal pathogens. The mononuclear phagocyte system is a heterogeneous group of leukocytes composed of tissue-resident macrophages, dendritic cells and monocyte-derived cells that are critical in defense against pneumonia, but mechanisms that regulate their maintenance and function during infection are poorly defined. Macrophage-colony stimulating factor (M-CSF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…2 A). While most of these studies reported gene expression, IL-34 protein was described in the healthy murine lung and human skin, kidney, intestine, spleen, and brain (Baek et al, 2015;Bettina et al, 2016;Franzè et al, 2015;Greter et al, 2012;Lin et al, 2008). We also found that IL-34 protein was detectable across various mouse tissues, with highest expression in brain, skin, and lymph nodes ( Fig.…”
Section: Il-34 Receptorsmentioning
confidence: 54%
“…2 A). While most of these studies reported gene expression, IL-34 protein was described in the healthy murine lung and human skin, kidney, intestine, spleen, and brain (Baek et al, 2015;Bettina et al, 2016;Franzè et al, 2015;Greter et al, 2012;Lin et al, 2008). We also found that IL-34 protein was detectable across various mouse tissues, with highest expression in brain, skin, and lymph nodes ( Fig.…”
Section: Il-34 Receptorsmentioning
confidence: 54%
“…Alveolar macrophages, the resident responders to pathogens in the airways, are critical to the clearance of K. pneumoniae pneumonia [107, 108]. The activation state and polarization of these macrophages are important in this process, as macrophages in the M2b or anti-inflammatory state were more susceptible to infection [109, 110].…”
Section: Responses Of Macrophages and Monocytes To K Pneumoniae Infementioning
confidence: 99%
“…We used a well-described model of Klebsiella pneumonia caused by a virulent strain of bacteria, delivered directly into the trachea of sedated experimental mice (15,16). We first characterized the effect of Klebsiella pneumonia on iron metabolism in WT mice.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental bacterial pneumonia was induced as previously described (15,16), by intratracheal inoculation of 500-1,500 CFU of K. pneumoniae strain 43816 (American Type Culture Collection). In some experiments, 1,500 CFU of K. pneumoniae was delivered i.v.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation